Information Seeking Behaviour, Health Knowledge, Attitude and Practice of Patients in Hospital Besar Tengku Ampuan Rahimah, Klang, Selangor Darul Ehsan - Tunku Zainal Abidin, Tunku Zaidar (1995)
The purpose of this study was to analyze the various interrelated factors associated with health and information seeking behaviour of hypertensive patients. The population of this study consisted of 245 hypertensive patients listed for their appointments at Hospital Besar Tengku Ampuan Rahlmah, Klang Twenty five percent of hypertensives have been selected daily for 10 consecutive days excluding Saturday and Sunday Information was collected via a highly structured interview, in which the questionnaires were administered orally Independent variables Included in this study were age, sex, ethnic group, marial status, education level, Income, health knowledge level, attitude, beliefs, health behaviour and social network The dependent variables Included were sources of health information (television, radio, newspaper, magazine, doctor, paramedic, family and friends), their frequency of referral, reliability and perceived Influence Findings of this study indicated that the higher the educational level the higher was the health knowledge score of respondents. Overall, hypertensive had a positive attitude toward their disease and every patient was aware of the importance of controlling blood pressure. Patients with higher health knowledge scores reported a tendency to indulge in good health related behaviour. Knowledge was related to health behaviour. Interpersonal interaction was found to be more important than mass media in influencing dietary, exercise and health habits. Doctors were considered most reliable, most influential and were also regarded as the leading source of health information.